Preclinical studies on convalescent human immune plasma-derived exosome: Omics and antiviral properties to SARS-CoV-2 - GÜL, FETHİ (My University, 2022)
The scale of the COVID-19 pandemic forced urgent measures for the development of new therapeutics. One of these strategies is the use of convalescent plasma (CP) as a conventional source for passive immunity. Recently, there has been interest in CP-derived exosomes. In this report, we present a structural, biochemical, and biological characterization of our proprietary product, convalescent human immune plasma-derived exosome (ChipEXO), following the guidelines set forth by the Turkish Ministry of Health and the Turkish Red Crescent, the Good Manufacturing Practice, the International Society for Extracellular Vesicles, and the Gene Ontology Consortium. The data support the safety and efficacy of this product against SARS-CoV-2 infections in preclinical models.
Keywords: Yaşam Bilimleri; Temel Bilimler; Life Sciences; Natural Sciences; İmmünoloji; Yaşam Bilimleri (LIFE); IMMUNOLOGY; Life Sciences (LIFE); Genel İmmünoloji ve Mikrobiyoloji; General Immunology and Microbiology; Immunology; exosome; extracellular vehicles (EVs); COVID-19; SARS-CoV-2; convalescence plasma; viral treatment; ACUTE RESPIRATORY SYNDROME; VENTILATION; RESPONSES; VESICLES; exosome; extracellular vehicles (EVs); COVID-19; SARS-CoV-2; convalescence plasma; viral treatment